2014
DOI: 10.1155/2014/813045
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between IL-17A-Producing Cells and Regulatory T Cells during Ischemic Stroke

Abstract: Immune responses and inflammation are key elements in the pathogenesis of ischemic stroke (IS). Although the involvement of IL-17A in IS has been demonstrated using animal models, the involvement of IL-17A and IL-17-secreting T cell subsets in IS patients has not been verified, and whether the balance of Treg/IL-17-secreting T cells is altered in IS patients remains unknown. In the present study, we demonstrated that the proportion of peripheral Tregs and the levels of IL-10 and TGF-β were reduced in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…In humans, Tregs are elevated in the peripheral blood of patients on days 7 and 21 after acute ischemic stroke, suggesting that such adaptive changes are possibly related to their protective action against stroke-induced damages [22]. However, in contrast to these neuroprotective effects on stroke, a recent study indicates that the proportion of peripheral Tregs and the levels of IL-10 and TGF-␤ were significantly reduced along with the elevation of circulatory IL-17A-producing cells in patients at days 7 and 28 after ischemic stroke compared to controls [9]. Another study indicated that Foxp3 + Treg-depletion did not affect the infarct volume in MCAO mice [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, Tregs are elevated in the peripheral blood of patients on days 7 and 21 after acute ischemic stroke, suggesting that such adaptive changes are possibly related to their protective action against stroke-induced damages [22]. However, in contrast to these neuroprotective effects on stroke, a recent study indicates that the proportion of peripheral Tregs and the levels of IL-10 and TGF-␤ were significantly reduced along with the elevation of circulatory IL-17A-producing cells in patients at days 7 and 28 after ischemic stroke compared to controls [9]. Another study indicated that Foxp3 + Treg-depletion did not affect the infarct volume in MCAO mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive Tregs therapy can reduce infarct size, promote tissue repair, down-regulate deleterious pro-inflammatory cytokines and alleviate the dysfunction of ischemic stroke models [14]. Cytokines TGF-␤ and IL-10 were reported to have antiinflammatory and neuroprotective roles in ischemic stroke [9,21]. In humans, Tregs are elevated in the peripheral blood of patients on days 7 and 21 after acute ischemic stroke, suggesting that such adaptive changes are possibly related to their protective action against stroke-induced damages [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence in favour of such a mechanism in PSF is still weak. One study in particular reported reduced percentage of circulating regulatory T cells combined with increased systemic Th17 and proinflammatory cytokines and reduced anti-inflammatory cytokines 94. In addition, interferon-gamma, the cytokine primarily responsible for upregulating IDO, was not higher in stroke81 when compared with healthy controls.…”
Section: Mechanisms Of Psfmentioning
confidence: 99%
“…The disrupted balance between these 2 CD4+ T cell subsets, namely, an excess of pro-inflammatory Th17 cells relative to anti-inflammatory Treg cells, has been implicated in chronic inflammation and autoimmunity [72]. Preliminary evidence of an altered Th17/Treg balance in stroke was recently demonstrated [73]. Brain inflammation alters the functioning of hypothalamic orexin-secreting neurons and decreases the synthesis and activity of monoamine neurotransmitters (Fig.…”
Section: Post-stroke Fatigue and Depressionmentioning
confidence: 99%